2021
DOI: 10.23960/jsl29269-279
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Liquid Smoke Produced from Medang Wood (Cinnamomum sp.) against Schizophyllum commune

Abstract: The efficacy of liquid smoke obtained from medang wood (Cinnamomum sp.)against Schizophyllum commune fungus was evaluated. This study aims to evaluate the antifungal properties of liquid smoke from medang against S. commune fungus. Potato Dextrose Agar (PDA) medium was used to determine the efficacy of the liquid smoke of medang wood on S. commune fungus growth. Three kinds of liquid smoke were obtained from the pyrolysis of medang wood at 370, 400, and 430°C. The efficacy of liquid smoke from medang wood for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…Konsentrasi 1% hingga 3% memiliki daya hambat yang sangat efektif terhadap jamur di beberapa penelitian yang menggunakan asap cair dari berbagai jenis tanaman seperti medang (Cinnanomum sp.) pada konsentrasi asap cair 2,5% mampu menghambat pertumbuhan Schizophyllum commune sebesar 98,57% (Permana et al, 2021), konsentrasi asap cair ulin (Eusideroxylon zwageri) sebesar 0,34% memiliki penghambatan pertumbuhan Colletotrichum capsici sebesar 100% (Imaningsih et al, 2021), dan konsentrasi asap cair limbah (Nicotiana tabacum) mampu menghambat pertumbuhan miselium Sclerotinia sclerotiorum dan Rhizoctonia solani sebesar 100% (Sarrafi et al, 2019).…”
Section: Pembahasanunclassified
“…Konsentrasi 1% hingga 3% memiliki daya hambat yang sangat efektif terhadap jamur di beberapa penelitian yang menggunakan asap cair dari berbagai jenis tanaman seperti medang (Cinnanomum sp.) pada konsentrasi asap cair 2,5% mampu menghambat pertumbuhan Schizophyllum commune sebesar 98,57% (Permana et al, 2021), konsentrasi asap cair ulin (Eusideroxylon zwageri) sebesar 0,34% memiliki penghambatan pertumbuhan Colletotrichum capsici sebesar 100% (Imaningsih et al, 2021), dan konsentrasi asap cair limbah (Nicotiana tabacum) mampu menghambat pertumbuhan miselium Sclerotinia sclerotiorum dan Rhizoctonia solani sebesar 100% (Sarrafi et al, 2019).…”
Section: Pembahasanunclassified
“…Ramos et al (2020) suggested that the fungicidal activity of liquid smoke at 400°C from cattle manure could be attributed to phenolic compounds. Similarly, Permana et al (2021) stated that phenolics and acids in liquid smoke could donate to antifungal activity agent. They attained liquid smoke from Cinnamomum sp.…”
Section: Performance Of Growth Inhibition Against Schizophyllum Communementioning
confidence: 99%
“…penyusun asap cair dari kayu jelutung adalah fenol, diikuti oleh keton dan asam asetat. Kandungan fenol (1,06%) dan asam (6,44%) pada asap cair kayu medang dilaporkan juga memiliki daya hambat terhadap pertumbuhan S. commune (Permana et al, 2021).…”
Section: Pendahuluanunclassified